A prime example of hard-hard and soft-soft interactions: complexes between 4,7-dioxa-1,10-diazabicyclo[8.6.6]docosa-13,19-diyne and Li+, Na+, Cu+, Ag+, Cd2+, Hg2+ - Kunze, Andreas; Gleiter, Rolf; Rominger, Frank (European journal of inorganic chemistry, 2006)
The crystal structures of 4,7-dioxa-1,10-diazabicyclo[8.6.6]docosa-13,19-diyne (7), its N,N′-dioxide derivative 10 and the complexes of 7 with LiClO4, NaNO3, CuI and AgI triflate, Cd(NO3)2, and HgCl2 were investigated. The Li+ and Na+ ions reveal a strong interaction between the ether bridge and the nitrogen atoms of 7. The CuI ion prefers an interaction between the nitrogen centers and the alkyne units whereas the AgI ion interacts with the hard oxygen and nitrogen centers as well as with the alkyne units. The reaction of HgCl2 with 7 in the presence of water afforded a molecule which could be looked at as the intermediate of a mercury-catalyzed addition of water to the triple bonds. (© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2006)